The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.4310/joc.2018.v9.n1.a2
|View full text |Cite
|
Sign up to set email alerts
|

Teaching dimension, VC dimension, and critical sets in Latin squares

Abstract: A critical set in an n × n Latin square is a minimal set of entries that uniquely identifies it among all Latin squares of the same size. It is conjectured by Nelder in 1979, and later independently by Mahmoodian, and Bate and van Rees that the size of the smallest critical set is ⌊n 2 /4⌋. We prove a lower-bound of n 2 /10 4 for sufficiently large n, and thus confirm the quadratic order predicted by the conjecture. This improves a recent lower-bound of Ω(n 3/2 ) due to Cavenagh and Ramadurai.From the point of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Using the Latin trades constructed in Section of this paper, we show that scsfalse(nfalse)=Ωfalse(n3/2false). Although this does not improve the result in , we include it as an interesting application of the theory used to prove Theorem . Theorem The size of the smallest defining set of any Latin square of order n has size Ω(n3/2).…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Using the Latin trades constructed in Section of this paper, we show that scsfalse(nfalse)=Ωfalse(n3/2false). Although this does not improve the result in , we include it as an interesting application of the theory used to prove Theorem . Theorem The size of the smallest defining set of any Latin square of order n has size Ω(n3/2).…”
Section: Introductionmentioning
confidence: 89%
“…Until quite recently, the best known lower bound for large n was scsfalse(nfalse)n(logn)1/3/2 , which in turn improved results given in and . However, very recently this has been improved by Hatami and Qian () who have shown that scsfalse(nfalse)104n2 for sufficiently large n .…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Vapnik-Chervonenkis dimension [31,32], or VC dimension for short, is a combinatorial parameter of major importance in discrete and computational geometry [9,17,19], statistical learning theory [7,32], and other areas [2,12,15,20]. The VC dimension of a family of binary vectors F ⊆ {0, 1} n is the largest cardinality of a set shattered by the family, that is, a set S ⊆ {1, .…”
Section: Introductionmentioning
confidence: 99%
“…SUPPORT VECTOR MACHINE LEARNING FOR ROLLER BEARING FAULT DIAGNOSIS PROCESSA. SUPPORT VECTOR MACHIMECorinna Cortes and Vapnik developed the currently used SVM technique to minimize the VC dimension[27][28][29][30][31]. The hyperplane, which separates data (…”
mentioning
confidence: 99%